Cathode material, preparation method thereof, cathode sheet and solid-state battery
Patent Information
- Application Number
- CN202611225946.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-13
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]本发明提供了一种正极材料及其制备方法和正极片、固态电池,旨在提供一种可以具有化学稳定性和三维Li+传输通道的材料,解决电池循环后界面阻抗的问题
本发明提供的单斜相LiαMX6或尖晶石相Li2M′X4晶体结构的卤化物快离子导体,其晶体结构中高氧化态的M位离子(如Zr4+、In3+、Sc3+等)或M′位离子(如Zn2+、Mg2+)与高电负性的卤素X离子形成了强离子键骨架和三维锂离子“高速通路”。本发明提供的包覆层材料对高电压正极材料基体在充电至高电位时具有更高的电化学氧化稳定性,形成了稳定的三维传输网络,能够始终保持与正极材料基体颗粒的紧密接触,避免了传统刚性包覆层因界面剥离而导致的离子传导“瓶颈”,降低了循环过程中界面阻抗的累积增长,实现了用于电池时长循环寿命与高倍率性能的协同提升。
Smart Images

Figure CN123017931A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and more specifically, to a cathode material, its preparation method, a cathode sheet, and a solid-state battery. Background Technology
[0002] Sulfide-based all-solid-state batteries utilize sulfide solid electrolytes such as Li6PS5Cl, combining high ionic conductivity with good mechanical ductility, making them a promising next-generation energy storage system. However, cathode materials (such as LiNi0.9Co0.)... 07 Mn0. 02 Inevitably, alkaline lithium salts (Li2CO3, LiOH, collectively referred to as "residual lithium") remain on the surface of O2. During battery preparation or operation, these residual lithiums often undergo irreversible acid-base reactions with sulfide electrolytes, generating high-resistivity interface products such as Li3PO4 and Li2S, while simultaneously releasing H2S and CO2 gases. This leads to a sharp increase in the impedance of the positive electrode / electrolyte interface and causes battery bulging failure, severely restricting the practical application of sulfide all-solid-state batteries.
[0003] Common improvement strategies in related technologies include constructing oxide coatings (such as LiNbO3, Al2O3, etc.) or coatings of specific functional materials (such as Li2ZrF6, Li5FeO4, etc.) on the cathode surface to physically isolate the direct contact between the cathode and the electrolyte. In addition, some researchers have used washing pretreatment to remove residual lithium compounds from the cathode surface, or used CO2 atmosphere treatment to regulate surface residual lithium. However, all of the above methods have limitations in practical applications. While washing can partially remove residual lithium, it is difficult to achieve complete removal without damaging the cathode surface structure; while oxide coatings can provide physical isolation, their own ionic conductivity is low, and side reactions may occur between the coating and the sulfide electrolyte; CO2 atmosphere treatment and other control methods require extremely high process precision, and excessively low or high residual lithium content will adversely affect battery performance.
[0004] Therefore, developing a material that can completely remove residual lithium at the interface while reducing the battery interface impedance has become a key technical problem that urgently needs to be solved in the field of sulfide all-solid-state batteries. Summary of the Invention
[0005] This invention provides a cathode material, its preparation method, a cathode sheet, and a solid-state battery, aiming to provide a material with chemical stability and three-dimensional Li + The material of the transmission channel addresses the issue of interface impedance after battery cycling.
[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution: A first aspect of the present invention provides a cathode material comprising: Cathode material matrix and coating layer; The coating layer covers at least a portion of the surface of the positive electrode material matrix; The coating layer comprises a fast ion conductor with a monoclinic phase LiαMX6 or a spinel phase Li2M′X4 crystal structure, wherein M comprises one or more of Zr, In, Sc, Y, Er, Ho, Tm, Yb, and Lu; M′ comprises one or more of Zn and Mg; X comprises one or more of F, Cl, Br, and I; and α is a value determined by the oxidation state of M, where α > 0.
[0007] As an optional implementation, the cathode material matrix satisfies at least one of the following conditions: (1) The cathode material matrix is a layered oxide; (2) The chemical formula of the cathode material matrix is LiNi Co γ Mn ρ O2, where β≥0.9, β+γ+ρ=1.
[0008] As an optional implementation, the thickness of the coating layer is 5nm~20nm.
[0009] As an optional implementation, the cathode material satisfies at least one of the following conditions: (1) The residual lithium content on the surface of the cathode material is 0.03wt%~0.08wt%; (2) The cathode material matrix and the coating layer are chemically bonded; (3) The X-ray diffraction pattern of the cathode material does not have a diffraction peak with 2θ of 27.9°~30.5°.
[0010] Secondly, the present invention provides a method for preparing a cathode material, comprising the following steps: Provide a cathode material matrix and detect the residual lithium content on the surface of the cathode material matrix; Metal halides and lithium source halides are provided based on the residual lithium content; The cathode material matrix, metal halide, and lithium source halide are mixed to obtain a mixture; The mixture is subjected to a first heat treatment at 300°C to 350°C to form an intermediate phase layer; then subjected to a second heat treatment at 450°C to crystallize the intermediate phase layer and form a fast ion conductor coating layer in situ to obtain the cathode material.
[0011] As an optional implementation, at least one of the following conditions is met: (1) The method for detecting the residual lithium content on the surface of the cathode material matrix includes chemical titration; (2) The residual lithium content on the surface of the cathode material matrix is 0.1wt%~1wt%; (3) The molar ratio of the metal halide to the residual lithium is (1~1.2):1; (4) The molar ratio of the metal halide to the lithium source halide is 1: (1~5).
[0012] As an optional implementation, at least one of the following conditions is met: (1) The heating rate of the first heat treatment is 0.5℃ / min to 3℃ / min; (2) The heating rate of the second heat treatment is 1℃ / min to 5℃ / min; (3) The processing time of the first heat treatment section is 1h to 5h; (4) The processing time for the second heat treatment is 3h~8h.
[0013] Thirdly, the present invention provides a positive electrode sheet, comprising the positive electrode material described above, or the positive electrode material prepared by the preparation method described above.
[0014] Fourthly, the present invention provides a solid-state battery, comprising the aforementioned positive electrode, negative electrode, and solid electrolyte.
[0015] As an optional embodiment, the solid electrolyte includes a sulfide electrolyte; the sulfide electrolyte includes Li6PS5Cl, Li6PS5Br, Li6PS5I, Li6PS5F, and Li 10 GeP2S 12 Li 10 SnP2S 12 Li7P3S 11 Li4P2S6, Li3PS4, Li 10 SiP2S 12 One or more of them.
[0016] The cathode material, its preparation method, cathode sheet, and solid-state battery provided by this invention have the following beneficial effects: The halide fast ion conductor with a monoclinic LiαMX6 or spinel phase Li2M′X4 crystal structure provided by this invention has M-site ions (such as Zr) in a high oxidation state in its crystal structure. 4+ In 3+ ,Sc 3+ (etc.) or M′ site ions (such as Zn) 2+ Mg 2+The coating material forms a strong ionic framework and a three-dimensional lithium-ion "high-speed pathway" with the highly electronegative halogen X ions. The coating material provided by this invention has higher electrochemical oxidation stability for high-voltage cathode material substrates when charged to high potentials, forming a stable three-dimensional transport network that can always maintain close contact with cathode material substrate particles. This avoids the ion conduction "bottleneck" caused by interface peeling in traditional rigid coatings, reduces the cumulative increase of interface impedance during cycling, and achieves a synergistic improvement in battery cycle life and high-rate performance.
[0017] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Attached Figure Description
[0018] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used together with the following detailed description to explain the invention, but do not constitute a limitation thereof.
[0019] Figure 1 This is a scanning electron microscope image of the cathode material prepared in Example 1.
[0020] Figure 2 The image shows the EDS diagram of the cathode material prepared in Example 1.
[0021] Figure 3 The X-ray diffraction (XRD) patterns of the cathode materials prepared in Example 1 and Comparative Example 5 are shown. Detailed Implementation
[0022] To make the technical solution and beneficial effects of the present invention more apparent and understandable, a detailed description is provided below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Experimental methods in the following embodiments, unless otherwise specified, are generally performed under conventional experimental conditions. Unless otherwise specified, all reagents and raw materials used in this invention are commercially available.
[0023] In the following description, numerous specific details are set forth in order to provide a more thorough understanding of the invention. However, it will be apparent to those skilled in the art that the invention may be practiced without one or more of these details. In other instances, to avoid obscuring the invention, some technical features well-known in the art have not been described; that is, not all features of actual embodiments are described herein, nor are well-known functions and steps described in detail.
[0024] In the description of this invention, it should be noted that the terms "first," "second," etc., are used for descriptive purposes only and are not intended to indicate or imply relative importance.
[0025] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges or individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0026] Unless otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form new technical solutions.
[0027] Unless otherwise specified, all technical features and optional technical features of this invention can be combined to form new technical solutions.
[0028] Unless otherwise specified, the terms "comprising" and "including" as used in this invention can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0029] [Cathode Material] To address the technical problem of high interface impedance in solid-state batteries, embodiments of the present invention provide a cathode material, comprising: a cathode material matrix and a coating layer; The coating layer covers at least a portion of the surface of the positive electrode material matrix; The coating layer comprises a fast ion conductor with a monoclinic phase LiαMX6 or a spinel phase Li2M′X4 crystal structure, wherein M comprises one or more of Zr, In, Sc, Y, Er, Ho, Tm, Yb, and Lu; and M′ comprises one or more of Zn and Mg. X includes one or more of F, Cl, Br, and I; α is a value determined by the oxidation state of M, and α > 0.
[0030] The halide fast ion conductor with a monoclinic LiαMX6 or spinel phase Li2M′X4 crystal structure provided by this invention has a high oxidation state M-site element (such as Zr) in its crystal structure. 4+ In 3+ ,Sc 3+ (etc.) or M′ bit elements (such as Zn) 2+ Mg 2+The coating material formed a strong ionic framework and a three-dimensional lithium-ion "high-speed pathway" with the highly electronegative halogen X. The coating material provided by this invention exhibits higher electrochemical oxidation stability of the high-voltage cathode material matrix when charged to high potentials. When the cathode material matrix is in a high-charge state, and its highly oxidizing surface contacts the coating layer, the outer electron cloud of the halogen anions in the coating layer is constrained by the strong covalent framework, making charge transfer difficult and preventing oxidation and precipitation. This constructs a barrier at the molecular level that blocks electron tunneling and interfacial side reactions, effectively avoiding the space charge layer effect and interfacial degradation phase formation caused by direct contact between the cathode material matrix and the surrounding solid electrolyte, significantly improving the battery's initial coulombic efficiency. Furthermore, this stable three-dimensional transport network maintains close contact with the cathode material matrix particles, avoiding the ion conduction "bottleneck" caused by interfacial peeling in traditional rigid coating layers, reducing the cumulative increase in interfacial impedance during cycling, and achieving a synergistic improvement in battery cycle life and high-rate performance.
[0031] In this invention, the value of α is determined by the oxidation state of the element at the M site. When M contains only a +4 valence element (such as Zr), α = 2. For example, the monoclinic phase LiαMX6 can be Li2ZrF6. When M contains only a +3 valence element (such as one of In, Sc, Y, Er, Ho, Tm, Yb, or Lu), α = 3. For example, the monoclinic phase LiαMX6 can be Li3InCl6. When M contains multiple elements, the oxidation states of each element may be different. In this case, α is determined based on the average oxidation state (weighted average) of the elements at the M site, satisfying the following: α + (total oxidation number at M site) + 6 × (-1) = 0 Therefore, α can be an integer greater than 0 or a non-integer. As an example, M is Zr. 4+ With In 3+ When the mixture is in equimolar form, the average oxidation state is +3.5, then α = 2.5.
[0032] In this invention, "coating" is not limited to direct coating, but also includes indirect coating; that is, the coating layer can be directly coated on the positive electrode material substrate, and there can be one or more other structures between the coating layer and the positive electrode material substrate; further optionally, the coating layer is directly coated on the positive electrode material substrate, that is, there are no other structures between the coating layer and the positive electrode material substrate.
[0033] In one embodiment, the positive electrode material matrix is a layered oxide.
[0034] In this paper, the term "layered oxide" refers to a class of lithium transition metal oxide cathode materials with an O3 phase layered crystal structure. Specifically, the O3 phase layered metal oxide refers to a crystal lattice in which oxygen ions are cubically close-packed in an ABCABC pattern, and lithium ions occupy octahedral interstitial sites between the transition metal and oxygen layers, thus forming a layered structure characterized by sequentially stacked transition metal-oxygen and lithium-oxygen layers along the c-axis.
[0035] In one embodiment, the chemical formula of the cathode material matrix is LiNi. Co γ Mn ρ O2, where β≥0.9, β+γ+ρ=1.
[0036] In LiNi Co γ Mn ρ In O2, β≥0.9. As an example, β can be 0.9, 0.92, etc., and it must be controlled under the premise that β≥0.9, then β+γ+ρ=1.
[0037] It should be noted that the layered oxide cathode material matrix mentioned in this invention is not limited to unmodified lithium nickel cobalt manganese oxide materials with a specific stoichiometric ratio, but may also include materials after modification treatment. The modification treatment may include, for example, bulk doping modification and / or surface coating modification, as long as it does not significantly impair the capacity performance of the material and meets the objectives of this invention. In this invention, "layered oxide" or "cathode material matrix" should be interpreted broadly, encompassing various derivative material systems optimized by the aforementioned modification methods using high-nickel layered lithium nickel cobalt manganese oxide as the matrix.
[0038] Optionally, the cathode material matrix is an unmodified layered lithium nickel cobalt manganese oxide, characterized by a β value of not less than 0.9, to ensure that while providing high reversible specific capacity, the coating layer design of the present invention effectively overcomes the problems of high surface chemical activity and severe interfacial side reactions.
[0039] In one embodiment, the thickness of the coating layer is 5 nm to 20 nm; as an example, the thickness of the coating layer can be 5 nm, 7 nm, 10 nm, 12 nm, 15 nm, 17 nm, 18 nm, 20 nm, etc. In this invention, controlling the thickness of the coating layer is based on quantitative optimization of interfacial transport by considering the intrinsic high lithium-ion conductivity of the coating material and the surface chemical properties of the cathode material matrix. This thickness range ensures that the coating layer forms a continuous and dense coverage on the substrate surface, effectively blocking interfacial side reactions between the cathode and the solid electrolyte; simultaneously, it avoids the coating layer being too thin, causing uncovered areas to become interfacial degradation initiation points, inducing side reactions during charging and discharging that continuously consume active lithium; and it prevents the coating layer from being too thick, leading to an extended lithium-ion solid-phase diffusion path, increased interfacial charge transfer impedance, and an excessive introduction of inactive coating phase causing a decrease in the overall specific capacity of the cathode. This synergistically achieves a comprehensive performance improvement in substrate interfacial chemical stability, continuous coating layer protection, and rapid interfacial ion transport.
[0040] The coating thickness was tested using transmission electron microscopy. For detailed procedures, please refer to the national standard GB / T47182-2026.
[0041] In one embodiment, the residual lithium content on the surface of the cathode material is 0.03 wt% to 0.08 wt%; as an example, the residual lithium content on the surface of the cathode material can be 0.03 wt%, 0.04 wt%, 0.05 wt%, 0.06 wt%, 0.07 wt%, 0.08 wt%, etc. Further optionally, the residual lithium content on the surface of the cathode material is 0.03 wt% to 0.06 wt%. This residual lithium content is an important indicator for evaluating the integrity of the coating layer's coverage of the cathode material substrate surface and its chemical protection effect. The lower the residual lithium content, the more fully the coating layer covers the active sites on the cathode material substrate surface, and the better the suppression effect on interfacial side reactions. The residual lithium content on the surface of the cathode material provided by this invention is as low as below 0.06 wt%, indicating that the coating layer of this invention has excellent coating effect and a very good suppression effect on interfacial side reactions.
[0042] In this document, the term "residual lithium content" refers to the mass percentage of alkaline lithium salts remaining on the surface of the cathode material, including Li2CO3 and / or LiOH.
[0043] In one embodiment, the cathode material matrix and the coating layer are chemically bonded.
[0044] The cathode material matrix and the coating layer provided in this invention achieve chemical bonding through in-situ interfacial chemical reactions, forming MOZ bridge bonds (M is the coating layer metal such as Zr, and Z is the transition metal in the cathode material matrix such as Ni, Co, Mn) and MO-Li bridge bonds. This strong chemical connection ensures that the coating layer will not peel off due to changes in the volume of the cathode material matrix during electrochemical cycling, fundamentally guaranteeing the long-term stability of the interface.
[0045] In one embodiment, the X-ray diffraction pattern of the cathode material does not exhibit a diffraction peak with a 2θ range of 27.9° to 30.5°. XRD testing can be performed using a Rigaku X-ray diffractometer (Japan). XRD testing of the cathode material shows the absence of this 2θ range, indicating the absence of Zr or other oxide impurities.
[0046] Embodiments of the present invention also provide a method for preparing a positive electrode material, comprising the following steps: Provide a cathode material matrix and detect the residual lithium content on the surface of the cathode material matrix; Metal halides and lithium source halides are provided based on the residual lithium content; The cathode material matrix, metal halide, and lithium source halide are mixed to obtain a mixture; The mixture is subjected to a first heat treatment at 300°C to 350°C to form an intermediate phase layer; then subjected to a second heat treatment at 450°C to crystallize the intermediate phase layer and form a fast ion conductor coating layer in situ to obtain the cathode material.
[0047] The preparation method provided by this invention pre-detects the residual lithium content on the surface of the cathode material matrix, precisely matches the amounts of metal halide and lithium source halide according to the stoichiometric ratio, and employs a combination of first and second heat treatments. In particular, the first heat treatment stage involves a low-temperature pre-reaction, while the second heat treatment stage involves a high-temperature crystallization sintering process. This ensures that the residual lithium reacts fully with the metal halide and lithium source halide in the low-temperature range of 300℃~350℃, generating an amorphous lithium halide / metal oxyfluoride mesophase, and releasing CO2 and H2O for complete exhaust, eliminating the chemical corrosion sources of Li2CO3 and / or LiOH on the solid electrolyte. Furthermore, in the high-temperature range of 450~500℃, the mesophase rearranges into a monoclinic LiαMX6 or spinel Li2M′X4 fast ion conductor, allowing for controllable crystallization and preventing excessive metal halide from reacting with the cathode material matrix to generate inactive oxides and other impurities. The cathode material coating layer prepared by the method provided by this invention possesses both chemical stability and three-dimensional Li... + The transmission channel improves the initial coulombic efficiency of all-solid-state batteries while reducing the interface impedance after cycling.
[0048] In one embodiment, the method for detecting the residual lithium content on the surface of the cathode material matrix includes chemical titration.
[0049] Optionally, the chemical titration method is a one-step titration method, specifically including: adding a standard hydrochloric acid solution dropwise to a uniformly dispersed cathode material matrix suspension; at the titration endpoint pH=7.0, both LiOH and Li2CO3 are completely neutralized by HCl. In calculating the results, the total number of moles of HCl consumed is converted to the equivalent mass of Li2CO3 based on the stoichiometric relationship of the reaction Li2CO3 + 2HCl → 2LiCl + H2O + CO2, thereby obtaining the residual lithium content in Li2CO3 equivalents.
[0050] As an example, the method for determining the Li2CO3 content includes the following steps: Take 5.0 g of positive electrode material matrix, add 50 mL of deionized water, stir at 25℃ for 30 min and then filter; titrate the filtrate with 0.1 mol / L HCl standard solution to pH=7.0, and record the number of HCl moles consumed n(HCl). The residual lithium content C (wt%) is calculated according to formula (1): C=n(HCl)×M(Li2CO3) / (2×m0)×100% Formula (1) Where M(Li2CO3) = 73.89 g / mol, and m0 is the sample mass (5.0 g).
[0051] In one embodiment, the residual lithium content on the surface of the cathode material matrix is 0.1wt% to 1.5wt%.
[0052] In one embodiment, the molar ratio of the metal halide to the residual lithium is (1~1.2):1. As an example, the molar ratio of the metal halide to the residual lithium can be 1:1, 1.05:1, 1.1:1, 1.15:1, 1.2:1, etc.
[0053] In one embodiment, the molar ratio of the metal halide to the lithium source halide is 1:(1~5). As an example, the molar ratio of the metal halide to the lithium source halide can be 1:1, 1:2, 1:3, 1:4, 1:5, etc. Further optional, the molar ratio of the metal halide to the lithium source halide is 1:(2~4), and even more specifically, the molar ratio of the metal halide to the lithium source halide is 1:3.
[0054] In one embodiment, the heating rate of the first heat treatment is 0.5℃ / min to 3℃ / min, and the first heat treatment time is 1h to 5h. As an example, the heating rate of the first heat treatment can be 0.5℃ / min, 1℃ / min, 1.2℃ / min, 1.5℃ / min, 1.8℃ / min, 2℃ / min, 2.2℃ / min, 2.5℃ / min, 3℃ / min, etc.; the first heat treatment time can be 1h, 2h, 3h, 4h, 5h, etc.; further optionally, the heating rate of the first heat treatment is 1℃ / min to 3℃ / min, and the treatment time is 2h to 4h.
[0055] In one embodiment, the heating rate of the second heat treatment is 1℃ / min to 5℃ / min; the treatment time of the second heat treatment is 3h to 8h; as an example, the heating rate of the second heat treatment can be 1℃ / min, 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min, etc.; the treatment time of the second heat treatment can be 3h, 4h, 5h, 6h, 7h, 8h, etc.; further optionally, the heating rate of the second heat treatment is 2℃ / min to 4℃ / min; the treatment time of the second heat treatment is 4h to 7h.
[0056] It should be noted that the processing time refers to the holding time at the heat treatment temperature.
[0057] Embodiments of the present invention also provide a positive electrode sheet, comprising the above-described positive electrode material or the positive electrode material prepared by the above-described preparation method.
[0058] It should be understood that the positive electrode includes the aforementioned positive electrode material. Therefore, all the features and advantages described above regarding the "positive electrode material" also apply to this "positive electrode," and will not be repeated here.
[0059] In one embodiment, the method for preparing the positive electrode includes the following steps: The aforementioned positive electrode material, solid electrolyte, and conductive agent are mixed to obtain a composite positive electrode material. The obtained positive electrode material is then pressed into shape in a mold to obtain a positive electrode sheet.
[0060] Alternatively, the solid electrolyte may include a sulfide electrolyte.
[0061] Further optionally, the conductive agent includes, but is not limited to, at least one of conductive carbon black, acetylene black, carbon nanotubes, graphene, and vapor-grown carbon fibers.
[0062] Alternatively, the mass ratio of the positive electrode material, solid electrolyte, and conductive agent may be (65~85):(14~30):1.
[0063] Embodiments of the present invention also provide a solid-state battery, comprising the positive electrode, negative electrode and solid electrolyte described above.
[0064] In one embodiment, the solid electrolyte comprises a sulfide electrolyte; the sulfide electrolyte includes Li6PS5Cl, Li6PS5Br, Li6PS5I, Li6PS5F, and Li 10 GeP2S 12 Li 10 SnP2S 12 Li7P3S 11 Li4P2S6, Li3PS4, Li 10 SiP2S 12 One or more of them.
[0065] Further optionally, the sulfide electrolyte may be Li6PS5Cl.
[0066] In this invention, solid assembly is carried out in a glove box (O2 < 0.5 ppm, H2O < 0.5 ppm).
[0067] In one embodiment, the method for preparing the solid-state battery includes the following steps: S1: Preparation of composite cathode material: The above-mentioned cathode material, solid electrolyte and conductive agent are mixed to obtain a composite cathode material.
[0068] S2: Preparation of composite anode material: A composite anode material is obtained by mixing the negative electrode active material, solid electrolyte, and conductive agent.
[0069] S3: Battery Assembly: (1) Weigh the solid electrolyte and place it in the battery mold. Press it into an electrolyte sheet using 300~400MPa and hold the pressure for 1~5 minutes. (2) Place the composite positive electrode material on one side of the electrolyte sheet, apply pressure of 150~250MPa, and hold the pressure for 1~5min to obtain the positive electrode sheet; (3) Place the composite negative electrode material on the other side of the electrolyte sheet, apply pressure of 150~250MPa, and hold the pressure for 1~5min to obtain the negative electrode sheet; (4) The positive current collector, positive electrode sheet, solid electrolyte, negative electrode sheet and negative current collector are stacked from top to bottom, and then pressurized and packaged under a pressure of 100~200MPa to obtain a solid battery.
[0070] In one embodiment, the solid-state battery preparation method can also omit the composite cathode material preparation process and directly use the cathode sheet prepared in the above embodiment.
[0071] Since the solid-state battery provided in this embodiment of the invention adopts all the technical solutions of the above embodiments, it has at least all the beneficial effects brought about by the technical solutions of the above embodiments, and will not be described in detail here.
[0072] The present invention will be specifically described below with reference to examples, but the implementation and protection of the present invention are not limited thereto. The following embodiments are only some embodiments of the present invention and are not intended to limit the present invention.
[0073] The present invention will be further described in detail below through examples. All raw materials used in the examples are commercially available.
[0074] Example 1 (NCM90@Li2ZrF6) (1) Preparation of cathode material: S1: Provides the LiNi cathode material matrix 0.9 Co 0.08 Mn 0.02 O2 (NCM90), 5.0g of positive electrode material matrix was weighed, and the residual lithium content (in Li2CO3 equivalent, wt%) was determined by chemical titration to be 0.82wt% (corresponding to residual lithium equivalent n=0.555mmol). S2: Provide metal halides and lithium source halides according to the residual lithium content: Based on the ratio of n(metal halide-ZrF4):n(residual lithium equivalent) = 1.05:1.0, the molar amount of ZrF4 is 11.655 mmol (1.95 g); the molar ratio of ZrF4 to lithium source halide (LiF) is 1:2, that is, the molar amount of LiF is 23.31 mmol (0.6 g).
[0075] Weigh 100 g NCM90, 0.6 g LiF, and 1.95 g ZrF4, and ball mill them together for 2 hours to obtain a mixture. S3: The mixture is heated to 320°C at a rate of 2°C / min and held for 3 hours (first heat treatment stage) to form an intermediate phase layer; then the mixture is heated to 480°C at a rate of 3°C / min and held for 5 hours (second heat treatment stage) to crystallize the intermediate phase layer and form a fast ion conductor coating layer in situ. After natural cooling, the mixture is sieved to obtain the positive electrode material.
[0076] The prepared cathode material was subjected to energy-dispersive X-ray spectroscopy (EDS) testing (using an energy-dispersive X-ray spectrometer; results are shown in [link to results]). Figure 2 ,pass Figure 2 It can be seen that F and Zr elements were detected, indicating that the nickel-cobalt-manganese cathode material provided in Example 1 has formed a fluorine- and zirconium-containing surface coating.
[0077] The prepared cathode material was subjected to SEM testing, and the SEM showed that the surface was smooth and free of impurities (see...). Figure 1 Furthermore, XRD testing showed no ZrO2 impurity phase peaks (see...). Figure 3 ).
[0078] (2) Preparation of solid-state batteries The positive electrode material, Li6PS5Cl, and vapor-grown carbon fiber (VGCF) of this embodiment were ground at a mass ratio of 70:29:1 for 30 min to obtain a composite positive electrode material. The negative electrode material (graphite negative electrode with a conventional charging capacity of 350mAh / g), Li6PS5Cl, and VGCF were ground at a mass ratio of 70:29:1 for 30 min to obtain a composite negative electrode material. 80 mg of Li6PS5Cl solid electrolyte was placed in a Φ10mm stainless steel mold and unidirectionally cold-pressed at 300MPa for 3 min to form an electrolyte intermediate layer. The stainless steel column of the mold battery was removed, and 18 mg of the composite positive electrode material was weighed and placed on top of the electrolyte intermediate layer. It was then cold-pressed at 350 MPa for 3 min to form a positive electrode composite sheet. Subsequently, the stainless steel base was removed, and 13 mg of the composite negative electrode material was weighed and placed on the other side of the electrolyte intermediate layer. It was then cold-pressed at 200 MPa for 3 min to form a negative electrode composite sheet.
[0079] The positive electrode current collector, positive electrode composite sheet, solid electrolyte intermediate layer, negative electrode composite sheet, and negative electrode current collector are stacked sequentially from top to bottom. After being embedded and positioned into a polyetheretherketone (PEEK) insulating sleeve, the stainless steel shell bolts are symmetrically tightened with a torque wrench, controlling the encapsulation pressure at 150 MPa to ensure tight adhesion between the layers. After encapsulation, the battery is left to stand in a glove box for 12 hours to eliminate residual stress and stabilize the solid-solid interface contact, resulting in a solid-state battery.
[0080] Example 2 (NCMA92@Li3InCl6) (1) Preparation of cathode material: S1: Provides the LiNi cathode material matrix 0.92 Co 0.06 Mn 0.02 O2 (NCMA92), 5.0g of positive electrode material matrix was weighed, and the residual lithium content (in Li2CO3 equivalent, wt%) was determined by chemical titration to be 1.15wt% (corresponding to residual lithium equivalent n=0.778mmol). S2: Provide metal halides and lithium source halides according to the residual lithium content: Based on the ratio of n(metal halide-InCl3):n(residual lithium equivalent) = 1.1:1.0, the molar amount of InCl3 is 17.12 mmol (3.79 g); the molar ratio of InCl3 to lithium source halide (LiCl) is 1:3, that is, the molar amount of LiCl is 17.4 mmol (2.18 g).
[0081] Weigh 100g NCMA92, 3.79g InCl3, and 2.18g LiCl, and ball mill them together for 2 hours to obtain a mixture. S3: The mixture is heated to 320°C at a rate of 2°C / min and held for 3 hours (first heat treatment stage) to form an intermediate phase layer; then the mixture is heated to 480°C at a rate of 3°C / min and held for 5 hours (second heat treatment stage) to crystallize the intermediate phase layer and form a fast ion conductor coating layer in situ. After natural cooling, the mixture is sieved to obtain the positive electrode material.
[0082] The solid-state battery in this embodiment is prepared using the same method as in Embodiment 1.
[0083] Example 3 (NCM90@Li2ZnCl4) S1: Provides the LiNi cathode material matrix 0.9 Co 0.08 Mn 0.02 O2 (NCM90), 5.0g of positive electrode material matrix was weighed, and the residual lithium content (in Li2CO3 equivalent, wt%) was determined by chemical titration to be 0.82wt% (corresponding to residual lithium equivalent n=0.555mmol). The residual lithium equivalent in 100 g of cathode material matrix is 11.09 mmol.
[0084] S2: Calculated based on the stoichiometric ratio of spinel phase Li2ZnCl4 and n(ZnCl2):n(residual lithium) = 1.1:1.0: Weigh 100g NCM90, 1.66g ZnCl2, and 1.03g LiCl, place them in a planetary ball mill, and mix at 300rpm for 2 hours.
[0085] S3: The mixture is heated to 320°C at a rate of 2°C / min and held for 3 hours (first heat treatment stage) to form an intermediate phase layer; then the mixture is heated to 480°C at a rate of 3°C / min and held for 5 hours (second heat treatment stage) to crystallize the intermediate phase layer and form a fast ion conductor coating layer in situ. After natural cooling, the mixture is sieved to obtain the positive electrode material.
[0086] Comparative Example 1 This comparative example directly uses NCM90 as the cathode material without any coating layer.
[0087] The solid-state battery in this comparative example is prepared using the same method as in Example 1.
[0088] Comparative Example 2 The specific implementation method of this comparative example is the same as that of Example 1. The difference from Example 1 is that in S3, the temperature is directly increased to 480℃ at 3℃ / min and held for 5 hours.
[0089] The solid-state battery in this comparative example is prepared using the same method as in Example 1.
[0090] Comparative Example 3 The specific implementation method of this comparative example is the same as that of Example 1, except that n(ZrF4):n(residual lithium equivalent) = 1.58:1.0.
[0091] The solid-state battery in this comparative example is prepared using the same method as in Example 1.
[0092] Comparative Example 4 The specific implementation method of this comparative example is the same as that of Example 1. The difference from Example 1 is that the first heat treatment stage in S3 is: the mixture is heated to 280°C at a rate of 2°C / min and kept at that temperature for 3 hours to form an intermediate phase layer.
[0093] The solid-state battery in this comparative example is prepared using the same method as in Example 1.
[0094] Comparative Example 5 The specific implementation method of this comparative example is the same as that of Example 1. The difference from Example 1 is that the second heat treatment stage in S3 is as follows: the temperature is increased to 580°C at 3°C / min and held for 5 hours to crystallize the intermediate phase layer, forming a fast ion conductor coating layer in situ. XRD testing is then performed, and the test results show the presence of ZrO2 impurity phase (test results are shown in [link to test results]). Figure 3 ).
[0095] The solid-state battery in this comparative example is prepared using the same method as in Example 1.
[0096] Comparative Example 6 The specific implementation method of this comparative example is the same as that of Example 1, except that: S2: Using NH4H2PO4 as the coating agent for coating, according to n(PO4) 3- ): n(residual lithium Li) + Weigh the NH4H2PO4 coating agent at a ratio of 1:3, and then ball-mill it with the positive electrode material matrix for 2 hours.
[0097] S3: Then, the temperature is increased to 500℃ at 2℃ / min, held for 6 h, and then naturally cooled to obtain the Li3PO4-coated NCM90 cathode material.
[0098] The solid-state battery in this comparative example is prepared using the same method as in Example 1.
[0099] Performance testing (1) Testing of cathode materials 1.1 Test of residual lithium content on the surface of cathode material: Take 5.0 g of the cathode material prepared in the examples and comparative examples, add 50 mL of deionized water, seal and stir at 25℃ for 30 min, and then filter. Titrate the filtrate with 0.1 mol / L HCl standard solution to pH=7.0, and calculate the residual lithium content (wt% as Li2CO3 equivalent). Each group was tested 3 times and the average was taken. The results are recorded in Table 1.
[0100] Table 1. Test results of residual lithium content in cathode materials
[0101] 2. XRD Testing of Cathode Materials: The cathode materials of Example 1 and Comparative Example 5 were ground and then transferred to a glass slide stage for scanning testing using a Rigaku X-ray diffractometer (Japan). The scanning range was 10°~80°, and the scanning speed was 5° / min. The test results are shown in [Figure Number]. Figure 3 .
[0102] (2) Battery performance test: The solid-state batteries prepared in the examples and comparative examples were subjected to constant current charge-discharge and cycle tests using the Blue Battery Test System. The voltage range was 2.5-4.3V. The test results are shown in Table 2.
[0103] 2.1 Discharge specific capacity / initial coulombic efficiency test method: The prepared battery was placed on the Xinwei Battery Testing Cabinet CTE-4064 and charged at a constant current of 0.1C to 4.25V. The charging specific capacity C0 of the solid-state battery was obtained by collecting test data. After standing for 15 minutes, it was discharged at 0.1C to 2.5V, and the discharge specific capacity C1 of the solid-state battery was obtained by collecting test data. The specific capacity at 0.1C is C1; the initial coulombic efficiency at 1C+0.1C is C1 / C0×100%; the test methods for the discharge capacity at 0.3C, 0.5C, and 1C are the same as those for 0.1C.
[0104] 2.2 Capacity Retention Rate Test Method: The prepared battery was placed on the Xinwei Battery Testing Cabinet CTE-4064. After two 0.1C charge-discharge cycles, the battery was charged at a constant current of 0.5C to 4.25V, and then charged at a constant voltage of 4.25V until the current ≤0.05C. The charging specific capacity C0 of the solid-state battery was obtained by collecting the test data. After standing for 15 minutes, it was discharged at 0.5C to 2.5V, and the discharge specific capacity C1 of the solid-state battery was obtained by collecting the test data. After standing for 15 minutes, this step was repeated n times to obtain the discharge specific capacity Cn. The capacity retention rate at 1C after 50 repetitions is C50 / C0×100%.
[0105] 2.3 Cyclic Impedance Test: The tests were conducted using an electrochemical workstation equipped with an AC impedance module in a constant temperature environment of 25℃ ± 0.5℃. All AC impedance measurements were performed at the battery open-circuit voltage (OCV) state, with a sinusoidal AC perturbation of 5mV applied, and the frequency sweep range was from 1 MHz to 10 mHz, with 10 points taken at each order of magnitude frequency.
[0106] The specific testing process is as follows: (1) Formation and initial impedance (R0) measurement The assembled battery was charged at a constant current rate of 0.1C to the upper cutoff voltage (e.g., 4.2V), then switched to constant voltage charging until the current dropped to 0.05C, and finally discharged at 0.1C to the lower cutoff voltage (e.g., 2.5V). This charge-discharge cycle was repeated twice to complete the formation. After formation, the battery was placed in a discharged state (voltage ≈ 2.5V) and left to stand at 25°C for 12 hours until the voltage stabilized. Electrochemical impedance spectroscopy (EIS) was then performed using the parameters described above to obtain the initial AC impedance spectrum. The EIS was then calculated using ZView or equivalent fitting software with R... s (Q1R1)(Q2R2)W equivalent circuit (where R s R1 is the surface film resistance, R2 is the interfacial charge transfer resistance, and W is the Warburg diffusion impedance. The Nyquist plot is subjected to nonlinear least-squares fitting to extract the initial interfacial resistance value, denoted as R0. 2,0 , which serves as the interface impedance before cycling.
[0107] (2) Loop testing The battery that has completed the initial impedance test is placed under a constant temperature of 25°C and charged at a constant current and constant voltage of 1C to the upper limit cutoff voltage (e.g., 4.2V) with a cutoff current of 0.05C. Then it is discharged at a constant current of 1C to the lower limit cutoff voltage (e.g., 2.5V). This process is repeated 50 times.
[0108] (3) Impedance after cycling (R) 50 )Measurement After the 50th cycle, the battery was discharged at 1C to 2.5V and left to stand at 25°C for 2 hours until the voltage stabilized. Then, the electrochemical impedance spectroscopy was tested using the same parameters as in step (1) to obtain the AC impedance spectrum after cycling. Similarly, R... s The equivalent circuit (Q1R1)(Q2R2)W is fitted to the Nyquist spectrum, and the interface charge transfer resistance R2 after cycling is extracted. This is the interface impedance after cycling listed in Table 2.
[0109] The method for extracting R2 is as follows: In the Nyquist spectrum, the second semicircle appearing in the mid-frequency region directly reflects the interface charge transfer process. The resistance value R2 corresponding to this semicircle is obtained by fitting an equivalent circuit, and the diameter of the semicircle (fitted value) represents the magnitude of the interface impedance. Throughout the entire test process, the fitting circuit and the initial values of the fitting parameters for the initial impedance and the impedance after cycling are kept consistent to ensure the comparability of the results.
[0110] Table 2: Battery Performance Test Results
[0111] As can be seen from the data in Table 1, the residual lithium content on the surface of the cathode material provided by the present invention is as low as less than 0.06 wt%, which is more than 95% lower than the residual lithium content of the uncoated cathode material (Example 1). This indicates that the coating layer of the present invention has excellent coating effect and good suppression effect of interfacial side reactions.
[0112] As can be seen from the data in Table 2, a comparison of the electrical performance test results of Examples 1-3 and Comparative Examples 1-6 shows that the cathode material provided by this invention, which has a fast ion conductor with a monoclinic phase LiαMX6 or spinel phase Li2M′X4 crystal structure as the coating layer, produces batteries with better first coulombic efficiency, cycle performance and lower interfacial impedance.
[0113] The cathode material in Comparative Example 1 was unmodified, and a solid-state battery was prepared using conventional cathode materials. The initial coulombic efficiency was only 82.3%, the capacity retention after 50 cycles was only 72.4%, and the impedance after cycling was 210 Ω, which is more than four times higher than that of the cathode material in the embodiments of this invention. Comparative Example 2 used a one-step sintering method, and the residual lithium content was 9.5 times that of Example 1. Due to the lack of a low-temperature pre-reaction stage, the residual lithium-halide reaction kinetics were insufficient, and the gas was trapped within the densification layer, resulting in incomplete conversion and an interface impedance as high as 118 Ω, with a cycle retention of only 84.2%. In Comparative Example 3, the metal halide was excessive, causing localized inactive aggregations in the coating layer during formation, leading to a decrease in the ionic conductivity of the coating layer and a rebound in impedance to 155 Ω. In Comparative Example 4, the temperature of the first heat treatment stage was reduced, resulting in a large amount of residual lithium remaining during the reaction process, with an interface impedance as high as 168 Ω and a capacity retention of over 80% after 50 cycles, failing to achieve the objectives of this invention. Comparative Example 6, under a fixed residual lithium condition, only consumed the original residual lithium, while the Li3PO4 coating layer used is an insulating / low-ionic-conductivity phase, which cannot provide Li in sulfide all-solid-state batteries. + Instead of creating a high impedance barrier at the cathode / electrolyte interface, the transport channel forms a high impedance barrier of up to 162Ω, resulting in a significant decrease in 1C capacity and cycle retention.
[0114] Example 1, under the same residual lithium removal level, exhibits a cycling impedance of only 42 Ω, an initial coulombic efficiency 4.6% higher than Comparative Example 6, and a 50-cycle capacity retention 11.7% higher than Comparative Example 6. This demonstrates that the present invention uses residual lithium as raw material, converting it in situ into a halide fast-ion conductor. The low-temperature pre-reaction in the first heat treatment stage ensures complete degassing and conversion of the residual lithium, while the high-temperature crystallization in the second heat treatment stage is controlled at ≤500℃ to suppress the formation of ZrO2 impurity phases. This results in a fast-ion conductor layer that possesses both chemical stability and ion conductivity.
[0115] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A positive electrode material, characterized in that, include: Cathode material matrix and coating layer; The coating layer covers at least a portion of the surface of the positive electrode material matrix; The coating layer comprises a fast ion conductor with a monoclinic phase LiαMX6 or a spinel phase Li2M′X4 crystal structure, wherein M comprises one or more of Zr, In, Sc, Y, Er, Ho, Tm, Yb, and Lu; M′ comprises one or more of Zn and Mg; and X comprises one or more of F, Cl, Br, and I. α is a value determined by the oxidation state of M, and α > 0.
2. The cathode material according to claim 1, characterized in that, The cathode material matrix satisfies at least one of the following conditions: (1) The cathode material matrix is a layered oxide; (2) The chemical formula of the cathode material matrix is LiNi Co γ Mn ρ O2, where β≥0.9, β+γ+ρ=1.
3. The cathode material according to claim 1, characterized in that, The thickness of the coating layer is 5nm~20nm.
4. The cathode material according to any one of claims 1 to 3, characterized in that, The cathode material satisfies at least one of the following conditions: (1) The residual lithium content on the surface of the cathode material is 0.03wt%~0.08wt%; (2) The cathode material matrix and the coating layer are chemically bonded; (3) The X-ray diffraction pattern of the cathode material does not have a diffraction peak with 2θ of 27.9°~30.5°.
5. A method for preparing a positive electrode material, characterized in that, Includes the following steps: Provide a cathode material matrix and detect the residual lithium content on the surface of the cathode material matrix; Metal halides and lithium source halides are provided based on the residual lithium content; The cathode material matrix, metal halide, and lithium source halide are mixed to obtain a mixture; The mixture is subjected to a first heat treatment at 300°C to 350°C to form an intermediate phase layer; then subjected to a second heat treatment at 450°C to crystallize the intermediate phase layer and form a fast ion conductor coating layer in situ to obtain the cathode material.
6. The preparation method according to claim 5, characterized in that, At least one of the following conditions must be met: (1) The method for detecting the residual lithium content on the surface of the cathode material matrix includes chemical titration; (2) The residual lithium content on the surface of the cathode material matrix is 0.1wt%~1wt%; (3) The molar ratio of the metal halide to the residual lithium is (1~1.2):1; (4) The molar ratio of the metal halide to the lithium source halide is 1: (1~5).
7. The preparation method according to claim 5, characterized in that, At least one of the following conditions must be met: (1) The heating rate of the first heat treatment is 0.5℃ / min to 3℃ / min; (2) The heating rate of the second heat treatment is 1℃ / min to 5℃ / min; (3) The processing time of the first heat treatment section is 1h to 5h; (4) The processing time for the second heat treatment is 3h~8h.
8. A positive electrode plate, characterized in that, It includes the cathode material according to any one of claims 1 to 4, or the cathode material prepared by the preparation method according to any one of claims 5 to 7.
9. A solid-state battery, characterized in that, It includes the positive electrode, negative electrode, and solid electrolyte as described in claim 8.
10. The solid-state battery according to claim 9, characterized in that, The solid electrolyte includes a sulfide electrolyte; the sulfide electrolyte includes Li6PS5Cl, Li6PS5Br, Li6PS5I, Li6PS5F, and Li 10 GeP2S 12 Li 10 SnP2S 12 Li7P3S 11 Li4P2S6, Li3PS4, Li 10 SiP2S 12 One or more of them.
